COMPARATION OF DENDROGRAM AND CLADOGRAM TOPOLOGY OF Gyrinops versteegii AND OTHERS GYRINOPS MEMBER FOR POLYPHASIC TAXONOMY - I Gde Adi Suryawan Wangiyana (Universitas Pendidikan Mataram, 2019)
The purpose of this research is to compare topology of dendrogram and cladogram of G. versteegii and others Gyrinops members for polyphasic taxonomy approach. Character of leaf, stem, flower and fruit of Gyrinops member were used for numeric phenetic analysis. On the other hands, trnL-trnF interspacer of chloroplast gene sequence were used for phylogenetic analysis. MVSP 3.1A were used for dendrogram construction using Simple Matching Coefficient and Jaccard’s Coefficient as clustering method. Co-stat cohor 6 were used for cophenetic correlation analysis. Multiple sequence alignment of trnL – trnF was carried by ClustalX 2.1 program. MEGA program was used for reconstruction of cladogram. This cladogram uses two different approach algorithms including: Neighbor Joining and Maximum Likelihood with 1000 bootstrap replication. Sequences similarity matrix analysis were carried by Phydit program with cut off value 99% for each Gyrinops members. Based on result, simple matching dendrogram has the same topology as Jaccard’s dendrogram. Cophenetic correlation analysis also confirm that there is no distortion on clustering analysis of these two dendrograms. On the other hand, Neighbor Joining cladogram has different topology from Maximum Likelihood cladogram. Similarity analysis of trnL-trnF sequence shows that each member of Gyrinops has strong phylogenetic relationship. Comparation of dendrogram and cladogram of G. versteegii with other Gyrinops members confirm that this species has different clustering group on dendrogram and cladogram. It could be concluded that G. versteegii has unique phylogenetic relationship and similarity relationship with others Gyrinops members.